A New Era for Teaching Heritage Languages to Bilingual Children in France - Hülya Sönmez L. Le Gac (Yaşadıkça Eğitim)
After the Second World War, a significant wave of immigration to France began, accelerating the spread of bilingual and multicultural societies within the country. This phenomenon has introduced a two-sided medallion issue concerning heritage language (minority language) education for the new generation of immigrant origin. On one side of the medallion is the necessity of providing heritage language education to bilingual children of immigrant origin, regardless of the circumstances. On the other side is the challenge of aligning heritage language education with France's educational policies and objectives while avoiding potential issues stemming from this phenomenon.  This study evaluates the recent developments in heritage language education for bilingual children in France from these two perspectives. To examine these developments from different angles, the transition from ELCO (Enseignement des Langues et Cultures d’Origine) to EILE (Enseignement International de Langues Étrangères) has been analyzed. A literature review identified that certain variables significantly influenced this transition, including political attitudes and approaches, the approach of teachers and educational infrastructure, changing educational objectives and the needs and expectations of immigrant families, the basic principles of education, and the dominance of French over regional and minority languages. To determine the impact of these factors, a detailed literature analysis was conducted, and the findings were used to explain these variables. Based on the results, the reasons for the transition from heritage language education to foreign language education were explored. Ultimately, the identified variables were found to play a significant role in shaping the EILE framework, which has fundamentally altered heritage language education. The analysis concluded that there is a need to develop student- and family-focused teaching processes to enhance EILE education, involving collaboration between France and the heritage (origin) countries.